A TiO2−x nanobelt array with oxygen vacancies: an efficient electrocatalyst toward nitrite conversion to ammonia. Issue 22 (28th February 2022) - Zhao, Donglin; Liang, Jie; Li, Jun; Zhang, Longcheng; Dong, Kai; Yue, Luchao; Luo, Yongsong; Ren, Yuchun; Liu, Qian; Hamdy, Mohamed S.; Li, Quan; Kong, Qingquan; et al.
Abstract : In situ grown TiO2 nanobelt array with oxygen vacancies on Ti plate acts as a high-efficiency and stable catalyst for electrochemical NO2 − reduction to NH3, attaining a large NH3 yield of 7898 μg h −1 cm −2 with a high faradaic efficiency of 92.7%. Abstract : Electrocatalytic nitrite reduction not only holds significant potential in the control of nitrite contamination in the natural environment, but also is an attractive approach for sustainable ammonia synthesis. In this communication, we report that a TiO2− x nanobelt array with oxygen vacancies on a titanium plate is able to convert nitrite into ammonia with a high faradaic efficiency of 92.7% and a large yield of 7898 μg h −1 cm −2 in alkaline solution. This monolithic catalyst also shows high durability with the maintenance of its catalytic activity for 12 h. Theoretical calculations further reveal the critical role of oxygen vacancies in nitrite electroreduction.